The contribution of innovation to farm-level productivity - Iordanis Parikoglou; Grigorios Emvalomatis; Doris Läpple; Fiona Thorne; Michael Wallace (Journal of Productivity Analysis, 2024)
Innovation is a key driver of productivity growth. This paper proposes a novel methodology in order to explore the impact of farm-level innovations on farm productivity and its components (i.e. technology, efficiency and scale) using representative data from Irish dairy farms. We measure innovation by an index based on employed production practices, continuous innovation activity and knowledge weighted by expert opinions. The results suggest that more innovative Irish dairy farmers are more productive. Specifically, all farmers improve their production technology and efficiency through their use of innovations, but farmers at specific levels of innovativeness may experience a decrease in productivity due to the small scale at which they operate. This indicates that innovation has a non-linear effect on productivity. We discuss the policy implications for reducing the unequal gains of innovation across farmers.
Keywords: D24; Q12; O33; 330; Agricultural Innovation System (AIS); Total factor productivity; Efficiency; Agriculture; Dairy production; Stochastic frontier analysis